Assessing the influence of Strategic Agility on the Performance of Selected Manufacturing Firms in South-South Nigeria. - Imagha, Orok A.; Okpara, Roy Maduabuchi; Eberechi, Ruth U.; Chukwunenye, Ihechukwumere (Research Journal of Humanities & Cultural Studies, 2024)
The purpose of this study was to assess the influence of strategic agility on selected manufacturing firms’ performance in South-south Nigeria. Strategic agility was proxied into core competencies and strategic sensitivity. Survey research design was adopted for the study. Population for the study was 319 staff of selected quoted manufacturing firms in South-South Nigeria. 177 was arrived at as sample size, using Taro Yamene’s formula for sample size determination. Primary and secondary sources of data were adopted for the study. Proportionate sampling technique was used to guarantee efficient representation of the selected firm while the research instrument was a structure questionnaire. Descriptive and Inferential statistics were used in analyzing the study. Findings showed that core competencies revealed a high correlation value of R = 0. 882 with an Unstandardized Coefficient Beta β=0.766. While strategic sensitivity revealed an Unstandardized Coefficient Beta of β=0.530. From the findings, it was concluded that strategic agility has a positive significant influence on selected manufacturing firms’ performance in South-south Nigeria. As recommendations, the studied manufacturing firms should imbibe core competency as a policy if they are to attain competitive advantage, being that core competencies are the foundation upon which a company builds its business and drives its success. Also, management of the selected studied manufacturing firms should develop strategic sensitivity as this will actively help in scanning the environment, and engaging in scenario planning exercises.